Discourse and literature - Cook, Guy (Oxford Univ. Press, 1994)
This study examines the relevance of schema theory to literary theory and the analysis of literary texts. Schema theory suggests that people understand texts and experiences by comparing them with stereotypical mental representations of similar cases. The new experience is then processed in terms of its deviation from that structure or its conformity to it. The book concludes with a section on pedagogical implications and an analysis of three well-known literary texts.